Adaptación de lentes progresivo en paciente masculino de 9 años con exceso de convergencia. - Parraga Mero, Priscila Elizabeth (2022)
Progressive glasses are multifocal lenses that are made of a single piece specially designed to compensate for the defects of presbyopia, such as some ametropia, such as myopia, hyperopia or astigmatism or those who only have tired eyes, see clearly at all distances, without sudden changes. is suitable for near, intermediate and distance vision, achieving maximum comfort. Convergence excess is a condition in which the patient is not able to maintain the coordination of the two eyes in near vision, prefers to deviate one eye inward (endophoria) during reading or when he gets too close to write. when performing activities in near vision. The clinical history of the patient presents difficulties with school tasks and as a result symptoms of headache, eye fatigue, everything is deteriorating with the visual health of the patient, the objective of this clinical case is to evaluate excess convergence by adapting progressive lenses. , for this reason the objective, subjective and complementary tests were carried out, in addition to the different tests to assess the Negative and positive relative amplitude measures, also the next point of convergence, it is very important to study the patient's ability to converge, these data obtained lead us to a diagnosis of this exposed case, finding as a result that he had a headache, visual fatigue and difficulty concentrating, especially when doing schoolwork, when manipulating the cell phone and when he has his virtual classes, after a detailed study of the optical examinations were determined as a conclusion of this case it is an excess of conversion gency accompanied by a refractive defect such as hyperopia and the use of positive additions will decrease near accommodation and endophoria, to eliminate the symptoms, the adaptation of progressive lenses was indicated as a treatment.